Hydrogel type lignocellulose-based photo-thermal evaporator and preparation method thereof

Through a hydrogel-type lignocellulose-based photothermal evaporator, the mixture of choline chloride and oxalic acid dihydrate and wood powder is used to form BLC photothermal materials, which solves the problem of insufficient performance of existing photothermal hydrogel materials. It has achieved efficient water resource purification and rapid decontamination effects, and promoted the sustainable utilization of solar energy.

CN119241870APending Publication Date: 2025-01-03SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411409463.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing photothermal hydrogel materials have low light absorption, poor photothermal conversion capacity, insufficient water transmission capacity and poor elastic properties, making it difficult to effectively use solar energy to purify water resources.

Method used

Using a hydrogel-type lignocellulose-based photothermal evaporator, the DES solvent is formed by choline chloride and oxalic acid dihydrate and mixing it with wood powder, destroying the hydrogen bond between lignin and cellulose, and forming BLC as a photothermal material A multi-layer composite material is formed with PVA hydrogel, which uses solar energy to drive water evaporation and generates water vapor by local heating.

Benefits of technology

It has achieved efficient solar energy and thermal energy conversion, fast water evaporation rate and excellent water resource purification capabilities, reduced energy losses and promoted the sustainable development of green and clean energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241870A_ABST
    Figure CN119241870A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps that BLC slurry with the dry weight being 16 wt% and a PVA solution are mixed to obtain a PVA / BLC precursor suspension, and then a hydrochloric acid solution and a glutaraldehyde solution are added into the PVA / BLC precursor suspension to obtain a cross-linked PVA / BLC precursor suspension; adding the PVA solution serving as a precursor solution into a hydrochloric acid solution and a glutaraldehyde solution to obtain a cross-linked PVA precursor suspension; and finally, performing directional freezing by adopting an ice template method to obtain the BFE evaporator. According to the prepared evaporator, under the condition that the illumination intensity is 1 kW / m < 2 >, the water evaporation rate reaches 2.36 kg / m < 2 > / h, and the energy efficiency is 92.8%. The water resource purification capacity and the rapid decontamination effect are excellent, dual utilization of waste biomass resources and solar resources is reflected, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a photothermal evaporator, in particular to a water-treated biomass hydrogel, and specifically to a hydrogel-type lignocellulose-based photothermal evaporator and a preparation method thereof. Background Art

[0002] According to statistics, there are 1.45 billion cubic kilometers of water on the earth, and fresh water resources account for only 2.5% of the total water volume. Only 1% of the water can be directly used by humans. With the development of human civilization, the importance of clean water resources has become increasingly prominent. At present, traditional water purification methods such as distillation, reverse osmosis and ion exchange have complex treatment processes, high energy consumption and are difficult to apply on a large scale. As a representative of clean energy, solar thermal materials have gradually become the key to coping with the water resource crisis due to their sustainability and environmental advantages. These materials can convert sunlight into thermal energy for water evaporation and purification. However, existing photothermal water gel materials have problems such as low light absorption, poor photothermal conversion ability, insufficient water transmission capacity and poor elastic properties. Summary of the invention

[0003] The purpose of the present invention is to provide a hydrogel-type lignocellulose-based photothermal evaporator and a preparation method thereof. The preparation process of the present invention is simple and the cost is low. The prepared hydrogel-type lignocellulose-based photothermal evaporator has excellent water resource purification ability and rapid decontamination effect.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] A method for preparing a hydrogel-type lignocellulose-based photothermal evaporator comprises the following steps:

[0006] Step 1: mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, heating and stirring in an oil bath at 100-120° C. to form a DES solvent;

[0007] Step 2: Add wood powder into DES solvent and deionized water at the same time, heat and stir in an oil bath until the wood powder is completely decomposed;

[0008] Step 3: After cooling to room temperature, add deionized water and stir, then centrifuge until the supernatant is colorless, and take out the precipitate to obtain a BLC slurry with a dry weight of 16 wt%;

[0009] Step 4: 1-3 g of BLC slurry is mixed with 4 mL of 2-5 wt% PVA solution to obtain a PVA / BLC precursor suspension, and then 100-150 μL of 1.2 mol / L hydrochloric acid solution and 50-100 μL of 25% glutaraldehyde solution are added to the PVA / BLC precursor suspension, and stirred evenly to obtain a cross-linked PVA / BLC precursor suspension;

[0010] Step 5: Take 16 mL PVA solution as a precursor solution, add 600-650 μL of 1.2 mol / L hydrochloric acid solution and 150-200 μL of 25% glutaraldehyde solution to obtain a cross-linked PVA precursor suspension;

[0011] Step 6: Pour the cross-linked PVA / BLC precursor suspension into a customized mold and freeze it to form the photothermal layer part, then pour the cross-linked PVA precursor suspension into the mold and freeze it to form the bottom water supply part; finally, place the directionally frozen mold in deionized water at room temperature to thaw, and the BFE evaporator can be obtained.

[0012] Furthermore, the heating time in step 1 is 30-60 minutes.

[0013] Furthermore, the wood powder in step 2 is wood powder with a particle size of ≥150 mesh converted from waste wood.

[0014] Furthermore, the temperature of the oil bath in step 2 is 110-120° C., and the heating time is 4-5 hours.

[0015] Furthermore, the number of centrifugation in step three is 3-5 times, and the centrifugal speed is 8000r / min.

[0016] Furthermore, the freezing temperature of the photothermal layer formed in step six is ​​-80°C, and the freezing time is 15-30 minutes.

[0017] Furthermore, the freezing time formed by the bottom water supply part in step six is ​​1-2 hours.

[0018] The present invention also provides a hydrogel-type lignocellulose-based photothermal evaporator, wherein the photothermal layer of the evaporator comprises a lamellar transverse structure and a network-like longitudinal structure.

[0019] Furthermore, the evaporator is heated to a light intensity of 1 kW / m 2 Under the condition of 2 / h, and the energy efficiency is 92.8%.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention forms a DES solvent by using choline chloride and oxalic acid dihydrate, and then mixes the DES solvent with wood powder to destroy the hydrogen bonds between lignin and cellulose, so that the wood powder is deconstructed, and the lignin is in situ regenerated and converted into BLC as a photothermal material to form a multilayer lignocellulose-based photothermal composite material with PVA hydrogel. The photothermal layer interface is applied to the solar-driven interfacial water evaporation, has a rapid photothermal response change, and fully utilizes the wood biomass resources of wood powder, avoiding the environmental pollution and resource waste caused by traditional treatment methods such as incineration and natural decay.

[0022] (2) The present invention adopts the photothermal material BLC as a new type of photothermal material, which can not only realize efficient solar energy and thermal energy conversion, but also form a porous network structure with hydrogel as a light absorber of the solar-driven interfacial evaporator. By locally heating water resources that cannot be directly utilized, water vapor is generated and collected, thereby obtaining clean water resources and alleviating the problem of clean water shortage.

[0023] (3) The present invention adopts clean energy solar energy. During the entire process of water evaporation, the light-heat conversion energy comes from solar energy, which is beneficial to long-term development, avoids the waste of non-renewable resources, reduces energy loss, and promotes the environmental protection and sustainable development of green and clean energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] FIG1( a ) is a SEM image of wood powder in Example 1 of the present invention;

[0025] FIG1( b ) is a SEM image of the black powder obtained after freeze-drying of the BLC slurry in Example 1 of the present invention;

[0026] Figure 2 This is a comparison chart of the FTIR spectra of the black powder and pure cellulose obtained after freeze-drying of the wood powder and BLC slurry in Example 2 of the present invention;

[0027] Figure 3 is the XRD spectrum of the black powder obtained after freeze-drying of the wood powder and BLC slurry in Example 3 of the present invention;

[0028] Figure 4 (a) shows the Na+ and Ca2+ concentrations before and after the BFE evaporator prepared in Example 4 of the present invention purifies seawater 2+ , schematic diagram of the concentration changes of K+ and Mg2+;

[0029] FIG4( b ) shows the Na+ and Ca+ of the BFE evaporator prepared in Example 4 of the present invention after purifying seawater. 2+ , K+, Mg2+ removal rate schematic diagram;

[0030] Figure 5Schematic diagram of water evaporation efficiency and energy efficiency of the BFE evaporator BFE prepared in Example 5 of the present invention at different salinities when the light intensity is 1kWm_2;

[0031] FIG6( a) is a schematic diagram of the decontamination capability of the BFE evaporator prepared in Example 6 of the present invention for MB solution when the light intensity is 1 kWm_2;

[0032] Figure 6(b) is a schematic diagram of the decontamination ability of the BFE evaporator prepared in Example 6 of the present invention for RB solution when the light intensity is 1kWm_2. DETAILED DESCRIPTION

[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0034] Example 1: A method for preparing a hydrogel-type lignocellulose-based photothermal evaporator is as follows:

[0035] Step 1: mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, heating in an oil bath at 100° C. for 30 min with stirring to form a DES solvent;

[0036] Step 2: Add wood powder with a particle size of ≥150 mesh converted from waste wood into DES solvent, add deionized water at the same time, heat in an oil bath at 120°C for 4 hours and stir until the wood powder is completely decomposed;

[0037] Step 3: After cooling to room temperature, add deionized water and stir, then centrifuge at 8000 r / min for 4 times until the supernatant is colorless, and take out the precipitate to obtain a BLC slurry with a dry weight of 16 wt%;

[0038] Step 4: 1.5 g of BLC slurry was mixed with 4 mL of 5 wt% PVA solution to obtain a PVA / BLC precursor suspension, and then 150 μL of 1.2 mol / L hydrochloric acid solution and 50 μL of 25% glutaraldehyde solution were added to the PVA / BLC precursor suspension, and stirred evenly to obtain a cross-linked PVA / BLC precursor suspension;

[0039] Step 5: Take 16 mL PVA solution as a precursor solution, add 600 μL of 1.2 mol / L hydrochloric acid solution and 200 μL of 25% glutaraldehyde solution to obtain a cross-linked PVA precursor suspension;

[0040] Step 6: Pour the cross-linked PVA / BLC precursor suspension into a customized mold and freeze it at -80°C for 15 minutes to form the photothermal layer. Then, pour the cross-linked PVA precursor suspension into the mold and freeze it for 1 hour to form the bottom water supply part. Finally, place the directionally frozen mold in deionized water at room temperature to thaw, and the BFE evaporator can be obtained.

[0041] The black powder obtained after freeze-drying of wood powder and BLC slurry was observed under a scanning electron microscope. As can be seen from Figure 1(a), the SEM image of the raw wood powder before treatment showed an ordered guided structure. The SEM image of the black powder in Figure 1(b) showed a more disordered and messy microstructure. This shows that the DES treatment led to the deconstruction and reorganization of the lignin structure in the wood powder, while retaining the cellulose crystals, thus forming a black wood-cellulose (BLC) material with specific light absorption characteristics.

[0042] Example 2: A method for preparing a hydrogel-type lignocellulose-based photothermal evaporator is as follows:

[0043] Step 1: mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, heating in an oil bath at 110° C. for 30 min with stirring to form a DES solvent;

[0044] Step 2: Add wood powder with a particle size of ≥150 mesh converted from waste wood into DES solvent, add deionized water at the same time, heat in an oil bath at 110°C for 4 hours and stir until the wood powder is completely decomposed;

[0045] Step 3: After cooling to room temperature, add deionized water and stir, then centrifuge at 8000 r / min for 3 times until the supernatant is colorless, and take out the precipitate to obtain a BLC slurry with a dry weight of 16 wt%;

[0046] Step 4: 1.0 g of BLC slurry was mixed with 4 mL of 5 wt% PVA solution to obtain a PVA / BLC precursor suspension, and then 150 μL of 1.2 mol / L hydrochloric acid solution and 50 μL of 25% glutaraldehyde solution were added to the PVA / BLC precursor suspension, and stirred evenly to obtain a cross-linked PVA / BLC precursor suspension;

[0047] Step 5: Take 16 mL PVA solution as a precursor solution, add 600 μL of 1.2 mol / L hydrochloric acid solution and 200 μL of 25% glutaraldehyde solution to obtain a cross-linked PVA precursor suspension;

[0048] Step 6: Pour the cross-linked PVA / BLC precursor suspension into a customized mold and freeze it at -80°C for 15 minutes to form the photothermal layer. Then, pour the cross-linked PVA precursor suspension into the mold and freeze it for 1 hour to form the bottom water supply part. Finally, place the directionally frozen mold in deionized water at room temperature to thaw, and the BFE evaporator can be obtained.

[0049] The black powder and pure cellulose obtained by freeze-drying wood powder and BLC slurry were analyzed by FTIR spectra. Figure 2 It can be seen that the black powder has absorption peaks at 1712cm-1, 1510cm-1 and 1442cm-1 in the FTIR spectrum, which correspond to the in-plane stretching vibration peaks of the CO bond, which is attributed to the vibration of the aromatic skeleton of lignin. At the same time, we can find that these peaks do not appear in the control of the pure cellulose sample, further proving the presence of lignin in the black powder. A new absorption peak appears at 1741cm-1, which corresponds to the carbonyl C=O stretching, proving that the cellulose hydroxyl group is partially esterified by oxalic acid during DES treatment. The stretching vibration peak of lignin at 1206cm-1 disappears, indicating that the deconstruction and reorganization of wood-cellulose are completed.

[0050] Example 3: A method for preparing a hydrogel-type lignocellulose-based photothermal evaporator is as follows:

[0051] Step 1: mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, heating in an oil bath at 100° C. for 60 min with stirring to form a DES solvent;

[0052] Step 2: Add wood powder to DES solvent and deionized water, heat in an oil bath at 120°C for 5 h and stir until the wood powder is completely decomposed;

[0053] Step 3: After cooling to room temperature, add deionized water and stir, then centrifuge at 8000 r / min for 4 times until the supernatant is colorless, and take out the precipitate to obtain a BLC slurry with a dry weight of 16 wt%;

[0054] Step 4: 2.0 g of BLC slurry was mixed with 4 mL of 2.5 wt% PVA solution to obtain a PVA / BLC precursor suspension, and then 150 μL of 1.2 mol / L hydrochloric acid solution and 50 μL of 25% glutaraldehyde solution were added to the PVA / BLC precursor suspension, and stirred evenly to obtain a cross-linked PVA / BLC precursor suspension;

[0055] Step 5: Take 16 mL PVA solution as a precursor solution, add 600 μL of 1.2 mol / L hydrochloric acid solution and 200 μL of 25% glutaraldehyde solution to obtain a cross-linked PVA precursor suspension;

[0056] Step 6: Pour the cross-linked PVA / BLC precursor suspension into a customized mold and freeze it at -80°C for 20 minutes to form a photothermal layer. Then, pour the cross-linked PVA precursor suspension into the mold and freeze it for 1.5 hours to form a bottom water supply part. Finally, place the directionally frozen mold in deionized water at room temperature to thaw, and the BFE evaporator can be obtained.

[0057] The XRD spectrum analysis of the black powder obtained after freeze-drying of wood powder and BLC slurry showed that Figure 3 It can be seen that although DES treatment leads to the deconstruction and reorganization of the lignin structure in wood powder, it does not destroy the crystalline structure of cellulose. The cellulose content in the black powder is relatively increased, which is due to the removal of other components (such as hemicellulose and amorphous cellulose) during the treatment process.

[0058] Example 4: A method for preparing a hydrogel-type lignocellulose-based photothermal evaporator is as follows:

[0059] Step 1: mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, heating in an oil bath at 120° C. for 30 min with stirring to form a DES solvent;

[0060] Step 2: Add wood powder with a particle size of ≥150 mesh converted from waste wood into DES solvent, add deionized water at the same time, heat in an oil bath at 120°C for 4 hours and stir until the wood powder is completely decomposed;

[0061] Step 3: After cooling to room temperature, add deionized water and stir, then centrifuge at 8000 r / min for 5 times until the supernatant is colorless, and take out the precipitate to obtain a BLC slurry with a dry weight of 16 wt%;

[0062] Step 4: 2.5 g of BLC slurry was mixed with 4 mL of 2 wt% PVA solution to obtain a PVA / BLC precursor suspension, and then 150 μL of 1.2 mol / L hydrochloric acid solution and 50 μL of 25% glutaraldehyde solution were added to the PVA / BLC precursor suspension, and stirred evenly to obtain a cross-linked PVA / BLC precursor suspension;

[0063] Step 5: Take 16 mL PVA solution as a precursor solution, add 600 μL of 1.2 mol / L hydrochloric acid solution and 200 μL of 25% glutaraldehyde solution to obtain a cross-linked PVA precursor suspension;

[0064] Step 6: Pour the cross-linked PVA / BLC precursor suspension into a customized mold and freeze it at -80°C for 30 minutes to form a photothermal layer. Then, pour the cross-linked PVA precursor suspension into the mold and freeze it for 1 hour to form a bottom water supply part. Finally, place the directionally frozen mold in deionized water at room temperature to thaw, and the BFE evaporator can be obtained.

[0065] The BFE evaporator was placed in seawater, and the purification capacity was tested based on the concentration changes of the main ions Na+, Ca2+, K+, and Mg2+ in the seawater. As shown in Figure 4(a), the concentrations of Na+, Ca2+, K+, and Mg2+ were greatly reduced before and after seawater purification, and the seawater after purification can meet the drinking water standards of the World Health Organization (WHO). As shown in Figure 4(b), the removal rates of Na+, Ca2+, K+, and Mg2+ in the purified water obtained by BFE evaporation treatment exceeded 99.8%, indicating that the BFE evaporator has extremely high purification efficiency in removing the main ions in seawater.

[0066] Example 5: A method for preparing a hydrogel-type lignocellulose-based photothermal evaporator is as follows:

[0067] Step 1: mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, heating in an oil bath at 100° C. for 45 min with stirring to form a DES solvent;

[0068] Step 2: Add wood powder to DES solvent and deionized water, heat in an oil bath at 115°C for 4 hours and stir until the wood powder is completely decomposed;

[0069] Step 3: After cooling to room temperature, add deionized water and stir, then centrifuge at 8000 r / min for 4 times until the supernatant is colorless, and take out the precipitate to obtain a BLC slurry with a dry weight of 16 wt%;

[0070] Step 4: 3 g of BLC slurry was mixed with 4 mL of 5 wt% PVA solution to obtain a PVA / BLC precursor suspension, and then 160 μL of 1.2 mol / L hydrochloric acid solution and 60 μL of 25% glutaraldehyde solution were added to the PVA / BLC precursor suspension, and stirred evenly to obtain a cross-linked PVA / BLC precursor suspension;

[0071] Step 5: Take 16 mL PVA solution as a precursor solution, add 600 μL of 1.2 mol / L hydrochloric acid solution and 200 μL of 25% glutaraldehyde solution to obtain a cross-linked PVA precursor suspension;

[0072] Step 6: Pour the cross-linked PVA / BLC precursor suspension into a customized mold and freeze it at -80°C for 15 minutes to form a photothermal layer. Then, pour the cross-linked PVA precursor suspension into the mold and freeze it for 2 hours to form a bottom water supply part. Finally, place the directionally frozen mold in deionized water at room temperature to thaw, and the BFE evaporator can be obtained.

[0073] At a light intensity of 1kWm -2 Under this condition, the BFE evaporator is placed in simulated brine with different mass fraction gradients to obtain water evaporation rate and energy efficiency at different salinities, such as Figure 5 As shown in the figure, it is not difficult to see from the evaporation rate of purified water with different salinities that after the addition of salt to the purified water resources, the evaporation rate dropped significantly, from 2.13 kg m-2h-1, 83.2% to 2.13 kg m-2h-1. -2 h -1 , 83.2%, and as the mass fraction of salt content in water increases, the evaporation effect also decreases. The reason is that when the salt water enters the BFE evaporator, the water molecules are heated through the interface of the photothermal layer to form water vapor and escape, but the salt cannot escape through the BFE evaporator and accumulates in the BFE evaporator, thus affecting the transmission rate of water molecules, resulting in insufficient water supply and decreased evaporation rate. However, we can conclude that although the evaporation rate of the BFE evaporator decreases, the evaporation efficiency of different solutions shows high stability, and the BFE evaporator has a strong practical advantage in obtaining clean water resources.

[0074] Example 6: A method for preparing a hydrogel-type lignocellulose-based photothermal evaporator is as follows:

[0075] Step 1: mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, heating in an oil bath at 100° C. for 30 min with stirring to form a DES solvent;

[0076] Step 2: Add wood powder with a particle size of ≥150 mesh converted from waste wood into DES solvent, add deionized water at the same time, heat in an oil bath at 120°C for 5 hours and stir until the wood powder is completely decomposed;

[0077] Step 3: After cooling to room temperature, add deionized water and stir, then centrifuge at 8000 r / min for 3 times until the supernatant is colorless, and take out the precipitate to obtain a BLC slurry with a dry weight of 16 wt%;

[0078] Step 4: 3 g of BLC slurry was mixed with 4 mL of 5 wt% PVA solution to obtain a PVA / BLC precursor suspension, and then 150 μL of 1.2 mol / L hydrochloric acid solution and 50 μL of 25% glutaraldehyde solution were added to the PVA / BLC precursor suspension, and stirred evenly to obtain a cross-linked PVA / BLC precursor suspension;

[0079] Step 5: Take 16 mL PVA solution as a precursor solution, add 620 μL of 1.2 mol / L hydrochloric acid solution and 180 μL of 25% glutaraldehyde solution to obtain a cross-linked PVA precursor suspension;

[0080] Step 6: Pour the cross-linked PVA / BLC precursor suspension into a customized mold and freeze it at -80°C for 15 minutes to form a photothermal layer. Then, pour the cross-linked PVA precursor suspension into the mold and freeze it for 2 hours to form a bottom water supply part. Finally, place the directionally frozen mold in deionized water at room temperature to thaw, and the BFE evaporator can be obtained.

[0081] At a light intensity of 1kWm -2 Under the condition of irradiation, the BFE evaporator was placed in MB solution and RB solution to test the decontamination ability, as shown in Figure 6(a) and Figure 6(b). In Figure 6(a), the BFE evaporator purifies the MB solution after 6 hours of illumination. The UV spectrophotometer detected that the characteristic absorption peak of MB dropped by half under the interfacial water evaporation driven by solar energy, and after 24 hours of illumination, the characteristic absorption peak of MB solution was almost consistent with that of pure water; similarly, it can be seen from Figure 6(b) that the rate of change of the characteristic absorption peak of RB solution is similar to that of MB solution, which shows that the BFE evaporator has a strong decontamination ability under the drive of sunlight.

[0082] The evaporator prepared by the present invention is subjected to a light intensity of 1 kW / m 2 Under the condition of 2 / h, and the energy efficiency is 92.8%. Its excellent water purification ability and rapid decontamination effect reflect the dual utilization of waste biomass resources and solar energy resources, optimize the use of resources, and reduce production costs. In addition, the present invention shows great development potential and application value in obtaining clean water resources using solar energy.

Claims

1. A method for preparing a hydrogel-type lignocellulose-based photothermal evaporator, characterized in that: The steps include: Step 1: mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, heating and stirring in an oil bath at 100-120° C. to form a DES solvent; Step 2: Add wood powder into DES solvent and deionized water at the same time, heat and stir in an oil bath until the wood powder is completely decomposed; Step 3: After cooling to room temperature, add deionized water and stir, then centrifuge until the supernatant is colorless, and take out the precipitate to obtain a BLC slurry with a dry weight of 16 wt%; Step 4: 1-3 g of BLC slurry is mixed with 4 mL of 2-5 wt% PVA solution to obtain a PVA / BLC precursor suspension, and then 100-150 μL of 1.2 mol / L hydrochloric acid solution and 50-100 μL of 25% glutaraldehyde solution are added to the PVA / BLC precursor suspension, and stirred evenly to obtain a cross-linked PVA / BLC precursor suspension; Step 5: Take 16 mL PVA solution as a precursor solution, add 600-650 μL of 1.2 mol / L hydrochloric acid solution and 150-200 μL of 25% glutaraldehyde solution to obtain a cross-linked PVA precursor suspension; Step 6: Pour the cross-linked PVA / BLC precursor suspension into a customized mold and freeze it to form the photothermal layer part, then pour the cross-linked PVA precursor suspension into the mold and freeze it to form the bottom water supply part; finally, place the directionally frozen mold in deionized water at room temperature to thaw, and the BFE evaporator can be obtained.

2. The method for preparing a hydrogel-type lignocellulose-based photothermal evaporator according to claim 1, characterized in that: The heating time in step 1 is 30-60 minutes.

3. The method for preparing a hydrogel-type lignocellulose-based photothermal evaporator according to claim 1, characterized in that: The wood powder in step 2 is wood powder with a particle size of ≥150 mesh converted from waste wood.

4. The method for preparing a hydrogel-type lignocellulose-based photothermal evaporator according to claim 1, characterized in that: The temperature of the oil bath in step 2 is 110-120° C., and the heating time is 4-5 hours.

5. The method for preparing a hydrogel-type lignocellulose-based photothermal evaporator according to claim 1, characterized in that: The number of centrifugation in step 3 is 3-5 times, and the centrifugal speed is 8000r / min.

6. The method for preparing a hydrogel-type lignocellulose-based photothermal evaporator according to claim 1, characterized in that: The freezing temperature of the photothermal layer formed in step 6 is -80°C, and the freezing time is 15-30 minutes.

7. The method for preparing a hydrogel-type lignocellulose-based photothermal evaporator according to claim 1, characterized in that: The freezing time formed by the bottom water supply part described in step 6 is 1-2h.

8. A hydrogel-type lignocellulose-based photothermal evaporator prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The photothermal layer part of the evaporator includes a lamellar transverse structure and a network-like longitudinal structure.

9. A hydrogel-type lignocellulose-based photothermal evaporator according to claim 1, characterized in that: The evaporator is heated at a light intensity of 1 kW / m 2 Under the condition of 2 / h, and the energy efficiency is 92.8%.